A comparison between artificial intelligence and traditional methods for creating podcasts as learning tools in health sciences - Lopez-Vazquez, AZ; Martinez-Guzman, MA; Toral-Murillo, María Valentina; Torres, Melissa Fernandez; Gonzalez-Ramos, IA (International Journal of Innovative Research and Scientific Studies, 2025)
The impact of Artificial Intelligence (AI) over the last decades is reflected in the diffusion of tools for automated learning and the availability of applications. Therefore, there is a need to study the risks and benefits of developing hard skills and critical thinking in health education, where tools such as podcasts have been employed to enhance learning. To determine whether the use of AI improves learning when developing a podcast about a health sciences-related topic, we conducted a cross-sectional analytical study with convenience sampling and a descriptive observational approach. We evaluated 52 health science students from a private university in Mexico using 10 questions related to the podcast topic. The assessment of learning, comparing students who used AI with a control group that performed traditional research, showed no significant differences in their mean grades (p = 0.81). The use of AI did not significantly compromise students’ learning. These results were further supported by students’ perceptions of their own learning, with most expressing positive opinions. AI may be implemented in health sciences education with positive reception by students.